pH-Responsive Drilling Fluid With High-Temperature and High-Density Performance - Li, Daqi; Jin, Junbin; Zhang, Dujie; Li, Fan; Wang, Xianguang; Liu, Lu (Frontiers in Earth Science, 2022)
Conventional drilling fluids experience the problems of a low cleanup efficiency and oily drilled cutting disposal. To resolve these problems, a type of pH-responsive drilling fluid with a temperature resistance of up to 150°C resistance a density of 1.5 g/cm3 was prepared using mixed emulsifiers. Stable reversion from a water-in-oil (W/O) emulsion to an oil-in-water (O/W) and vice versa was realized. The results of light backscattering and sag stability suggested that the W/O and O/W emulsion-based drilling fluids showed excellent resistance to coalescence or sedimentation. There was no demulsification or barite sedimentation during emulsion reversion. W/O and O/W emulsions exhibited small droplet sizes and uniform distributions. The properties of the W/O and O/W emulsion-based drilling fluids were similar even after hot rolling at 150°C for 16 h. The reversible drilling fluid showed excellent resistance to contamination by saline water and drilled cuttings. The residual W/O emulsion-based drilling fluid was cleaned with acids at a high efficiency. The oil content of the drill cuttings generated by the W/O emulsion-based drilling fluid was reduced using simple acids. The improved reversion stability with high temperature and density resistance makes it possible for applicable reversible drilling fluid in deep or ultra-deep wells required by different geological formation.